Analysis of noise-protective properties of sheet material composite structures - Саньков, Петр Николаевич; Макарова, Вера Николаевна; Ткач, Наталья Алексеевна; Гваджаиа, Бежан Джумберович (Technology audit and production reserves, 2016)
The object of this research is sound insulation properties of sheet material composite structures. The basis of the working hypothesis is the fact that particular importance has the minimum gap between the layers for the theoretical insulation calculations of the double sheet material structure. Dependence observation of the air gap size between the two layers of interior walls suggests that for maximum sound insulation ability the air gap size should be no less than five times greater than the maximum thickness of one of them. Comparison of the estimated sound insulation characteristics RN with the measured frequency response of air sound insulation R shows that the actual sound insulation of two sheet structure is significantly lower than estimated. This difference is between 3 to 5 dB over the entire frequency range. It also confirms the low acoustic efficiency of modern plastic windows. The results of this work will allow as a promising direction for further research to identify the program to adjust the sound insulation properties of any translucent walling (including window fillings), also consisting of sheet materials.